Tourism in a Unique Destination - Pelagia Moloni (ARCHive-SR, 2023)
Tourism in Antarctica has been dynamically developed in recent decades, although it is located in a small geographical part of continent. The main reason that visitors plan a trip to the destination, when the opportunity is given, is the natural landscape and wildlife. In addition, overheating of the planet that causes ice to melt has enhanced the feeling of fear as there is severe environmental concern for the coming years. Space and seasonal exclusions make it even more special and the tourist product which is offered by this continent is expensive and requires a lot of preparation. Tourism activity in such a fragile environment has sparked several reactions in the past, mainly from the scientific community, as it is the main recipient of the negative effects of tourism. Furthermore, organized efforts have been made so that the offered product will promote more environmentally friendly trips that will affect the ecosystem as little as possible.